PENGENALAN INTERNET SEBAGAI MEDIA PROMOSI USAHA KECIL DI KELURAHAN BUARAN SERPONG - Juhaeri, Juhaeri; Chasanah, Uswatun; Sofi’I, Imam; Nursyifa, Aulia (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of community service is to provide knowledge, and understanding of the introduction of the Internet as a medium for promoting small businesses in entrepreneurship so as to produce maximum profits. Inform, and urge to help MSMEs in the Buaran Serpong Village, South Tangerang City in order to optimize internet technology in marketing products. The community service methods are seminars and discussions. Participants in the community service activities are UKM around the Ni'matul Ittihad mosque in Buaran District, RT. 02/03 Serpong, South Tangerang. The results of this community service are all participants who consider, and apply all the material and discussions that occur during the event so that the business objectives can be increased by maximizing profits. Output targets to be achieved are participants can use the internet as a medium for business promotion, provide opportunities for small businesses that connect networks, business information for customers and the community, provide services to customers better by providing interesting and interactive information, increasing public interest in products, for sale or place of transaction, moving global markets, can be made media information advice, company publications and promotions.